Stereochemistry of organic compounds - Eliel, Ernest L.; Wilen, Samuel H. ([S.l.] : Wiley-Interscience, 1994)
Stereochemistry of Organic Compounds The first fully referenced, comprehensive book on this subject in more than thirty years, Stereochemistry of Organic Compounds contains up-to-date coverage and insightful exposition of all important new concepts, developments, and tools in the rapidly advancing field of stereochemistry, including: * Asymmetric and diastereoselective synthesis * Conformational analysis * Properties of enantiomers and racemates * Separation and analysis of enantiomers and diastereoisomers * Developments in spectroscopy (including NMR), chromatography, and molecular mechanics as applied to stereochemistry * Prostereoisomerism * Conceptual foundations of stereochemistry, including terminology and symmetry concepts * Chiroptical properties Written by the leading authorities in the field, the text includes more than 4,000 references, 1,000 illustrations, and a glossary of stereochemical terms.